Multivariate p-Adic Fermionic q-Integral on ℤp and Related Multiple Zeta-Type Functions - Min-Soo Kim; Taekyun Kim; Jin-Woo Son (Abstract and Applied Analysis)
In 2008, Jang et al. constructed generating functions of the multiple twisted Carlitz's type q-Bernoulli polynomials and obtained the distribution relation for them. They also raised the following problem: “are there analytic multiple twisted Carlitz's type q-zeta functions which interpolate multiple twisted Carlitz's type q-Euler (Bernoulli) polynomials?” The aim of this paper is to give a partial answer to this problem. Furthermore we derive some interesting identities related to twisted q-extension of Euler polynomials and multiple twisted Carlitz's type q-Euler polynomials.